LEGAL PROTECTION FOR CUSTOMER OF BANKRUPT RURAL BANK (BPR) IN INDONESIA - Nola, Selvia; Basri, Suci Zalsabilah; Nur Hafiza, Sylvi (Jurnal Hukum Bisnis Bonum Commune, 2021)
AbstractProtection of rural credit bank customers as consumers is intended so that customers have the right to file complaints and use banking mediation forums to be able to resolve disputes in the banking sector simply, cheaply, and quickly.  Customer protection is also needed so that when an unwanted thing occurs, such as bankruptcy, it can be immediately resolved by a legal entity that helps resolve the problem.  The research method of this paper uses the method normative research with literature study conducted through books, references, journals, results of previous research, related to the issues under study, namely based on the Banking Law and the Civil Code.  Customer legal protection, viewed also from consumer protection laws and forms of customer legal protection, is a guarantee of legal certainty for customers to be protected and to receive correct, clear, and honest services regarding the conditions and guarantees of services provided.Keywords: bankruptcy; consumer; protectionAbstrakPerlindungan nasabah BPR sebagai konsumen dimaksudkan agar nasabah memiliki hak untuk mengajukan pengaduan dan menggunakan forum mediasi perbankan untuk dapat menyelesaikan sengketa di bidang perbankan secara sederhana, murah, dan cepat. Perlindungan nasabah juga diperlukan agar bila terjadi hal yang tidak diinginkan seperti kebangkrutan dapat segera diselesaikan oleh badan hukum yang membantu menyelesaikan masalah tersebut. Metode penelitian menggunakan metode penelitian normatif dengan studi pustaka yang dilakukan melalui buku, referensi, jurnal, hasil penelitian sebelumnya, terkait dengan permasalahan yang diteliti yaitu berdasarkan Hukum Perbankan dan Hukum Perdata. Perlindungan hukum pelanggan, dilihat juga dari hukum perlindungan konsumen dan bentuk perlindungan hukum pelanggan, merupakan jaminan kepastian hukum bagi pelanggan untuk dilindungi dan mendapatkan layanan yang benar, jelas, dan jujur mengenai kondisi dan jaminan layanan yang diberikan.